Rubber (Latex) Cutting Process Considering the Cost of the Double Cut Alternative (DCA) Process in Human and Robot Collaboration - Akbar, Adi; Ma'ruf, Anas (Journal of Research in Industrial Engineering and Management, 2024)
Technological developments allow human-robot collaboration resources to be carried out in the rubber (latex) cutting process in plantations. The human-robot collaboration activities are carried out simultaneously in each rubber tree but have different work tasks. Research regarding human-robot collaboration resource costs in the rubber (latex) cutting process activity is still minimal, so it is necessary to discuss and calculate the resource costs of human-robot collaboration by developing mathematical models. Research regarding the resource costs of human-robot collaboration in the rubber (latex) cutting process is still minimal, so discussion and calculations are needed with the development of mathematical models. Mathematical model development is not just a theoretical exercise. The practical goal is to minimize costs by considering human resources, robots, and human-robot collaboration. Through rigorous testing, we aim to minimize the cost of each resource. Test results show that human-robot collaboration resources can significantly influence cost minimization. Cost minimization is accomplished by programming an algorithm in optimization software. This program is used to make it easier to complete the optimal solution in terms of relatively fast time, which refers to the precedence diagram of the rubber (latex) cutting process.Based on the results of experimental data, the development of a mathematical model functions logically to solve resource placement problems, resulting in a minimum cost of IDR 1,618,234,564,595, total human resources of 1 person and robot resources of 1 unit.